Fulfillment of Accessibility Rights of Consumers with Disabilities in Banking Services - Daffa Alkafi (Proceedings Series on Social Sciences & Humanities, 2023)
Accessibility in public services should be owned in every public service building facility to make it easier for people with disabilities to carry out public service activities. The problem behind the author is the difficulty of persons with disabilities in accessing banking services where the rights of persons with disabilities as stipulated in Law Number 4 of 1997 concerning Persons with Disabilities, Law Number 25 of 2009 concerning Public Services, Financial Services Authority Regulation Number 1 of 2013 concerning Consumer Protection in the Financial Services Sector, and Law Number 8 of 2016 concerning Persons with Disabilities states that financial service business actors are required to provide accessibility for persons with disabilities. The author formulates two problems, namely: how is the regulation of accessibility rights for persons with disabilities as a form of protection provided by the state and how are the accessibility rights for persons with disabilities in conducting public services in banking. The method used in this writing is a normative legal writing method that uses a legislative approach and literature study. This writing concludes that accessibility rights for persons with disabilities have been guaranteed by the state, especially in public services. Accessibility is needed by persons with disabilities in carrying out all their activities, especially in terms of public services in banking.